The rise of market-capitalism and the roots of anti-American terrorism - Tim Krieger; Daniel Meierrieks (Albert-Ludwigs-Universität Freiburg, Wilfried-Guth-Stiftungsprofessur für Ordnungs- und Wettbewerbspolitik, 2013)
We examine the role of market-capitalism in anti-American terrorism, differentiating between level- and rate-of-change-effects associated with market-capitalist development and their respective relationship with anti-U.S. violence. Using panel data for 149 countries between 1970 and 2007, we find that higher levels of capitalist development - consistent with the capitalist-peace literature - coincide with less anti-American terrorism, while the marketization process has inflammatory effects on anti-American terrorism. These findings are further corroborated by system-level time-series evidence. We argue that a higher level of market-capitalism is associated with less anti-American terrorism by creating economic interdependencies and a convergence of pro-peace values and institutions, while the destabilizing effects of the marketization process may stem from the violent opposition of various anti-market interest groups to economic, politico-institutional and cultural change initiated by a transition towards a market economy. These interest groups deliberately target the U.S. as the main proponent of modern capitalism, globalization and modernity, where anti-American terrorism serves the purpose of consolidating their respective societal position. Our findings that the U.S. may ultimately become a less likely target of transnational terrorism through the establishment of market economies, but should not disregard the disruptive political, economic and cultural effects of the marketization process in noncapitalist societies.
Keywords: 330; terrorism; anti-Americanism; capitalism; market economy; globalization